Knowledge and attitude of traditional medicine among Staff Nurse In Hospital Universiti Sains Malaysia (HUSM) - Affendy, Nur Aishah Eliza (Universiti Sains Malaysia, 2024)
This study investigates the levels of knowledge and attitudes towards traditional medicine (TM) among staff nurses at Hospital Universiti Sains Malaysia (HUSM). Utilizing a cross-sectional design, the research included nurses from various departments to provide a comprehensive overview of their perceptions. The findings revealed that while a majority of the nurses (59.6%) held positive attitudes towards TM, a significant portion (51.1%) exhibited poor knowledge about these practices. Statistical analysis demonstrated a significant association between the level of knowledge and attitudes towards TM, as well as with sociodemographic factors such as age, gender, years of experience, and income. These results highlight the need for targeted health education programs to enhance nurses' understanding of TM and address the gaps in their knowledge. The study underscores the importance of incorporating TM education into nursing curricula to foster a more holistic approach to patient care. Future research should focus on longitudinal studies to track changes over time and explore the impact of educational interventions on nurses' knowledge and attitudes towards traditional medicine.